Emergence of novel cephalopod gene regulation and expression through large-scale genome reorganization - Hannah Schmidbaur; Akane Kawaguchi; Tereza Clarence; Xiao Fu; Oi Pui Hoang; Bob Zimmermann; Elena A. Ritschard; Anton Weissenbacher; Jamie S. Foster; Spencer V. Nyholm; Paul A. Bates; Caroline B. Albertin; et al. (Nature Communications, 2022)
Cephalopods are an enigmatic animal group with complex and adaptive behaviors such as camouflage; however the genetic basis for these traits is not well understood. Here the authors reveal a set of cephalopod-restricted rearranged genomic loci, involving known neuronal regulators but also unexpected gene families, that confer topological organization and gene regulation.